A simple method of enrichment of honey powder with phytochemicals and its potential application in isotonic drink industry. (May 2020) - Tomczyk, Monika; Zaguła, Grzegorz; Dżugan, Małgorzata
Abstract: The aim of the study was to obtain honey powders enriched with plant extracts by spray drying method and to implement them in the production of dry concentrate of isotonic drinks. Multifloral honey and maltodextrin dissolved in plant (mint, nettle and beetroot) aqueous infusions were transformed into honey powders using spray dryer. Obtained powders were examined regarding antioxidant activity (DPPH and FRAP), phenolics compounds and mineral composition (ICP-OES). The same drying method was used for dry concentrates of isotonic drinks production. For this purpose homemade isotonic drinks prepared according to various recipes using honey and other natural components (plant infusions and/or fruit juices and salt) were subjected for drying. Aqueous solutions (9% w/w) of obtained concentrated powders were examined in terms of osmolality, caloric value, reducing sugars content, mineral composition (ICP-OES) and antioxidant activity (DPPH, FRAP and phenolic compounds). Using plant infusions as solvents, enriched honey powders in antioxidants (4–10 times) and minerals (especially K, Ca, Mg) as compared to control samples. Produced dry concentrates of natural isotonic drinks after re-dissolving in water gave beverages characterized by proper osmolality, caloric value and strongly enhanced antioxidant properties as compared to commercial counterparts. Highlights: The production of honey powder enriched with phytochemicals and minerals was proposed. The enriched honey powder can serve as functional food additive easy to modify. Natural isotonic drink dry concentrate can be obtained by developed technology. Isotonic drink from dry concentrate have higher antioxidant activity than commercial.